Heat stress and wounding response in expression and RNAi impact on Arabidopsis thaliana soluble pyrophosphatase isoforms - Ergen, Z. Neslihan; greiner, Steffen; Rausch, Thomas (İstanbul Kültür Üniversitesi, 2009)
Mature plants are assumed to lack cytoplasmic soluble pyrophosphatase activity and vacuolar membrane-bound proton-pumping pyrophosphatase is generally accepted as the sole enzyme responsible for the removal of pyrophosphate accumulated in the cytosol as a by-product of several biosynthetic pathways. On the contrary, Arabidopsis thaliana genome encodes six soluble pyrophosphatase isoforms, which were shown to be highly conserved both in nucleic and in amino acid sequences. There is only one isoform that is shown to be localized in plastids and there is no data available on the localization and/or possible expressional regulation of other isoforms. The analyses of the change in transcription of all A. thaliana soluble pyrophosphatases showed isoform-specific regulation, indicating the role of these isoforms during stress response. Furthermore, we have selected two isoforms through Digital Northern analysis derived from UniGene database and specifically knockdown these isoforms by RNAi approach. The results indicated that A. thaliana soluble pyrophosphatases have specific function in vivo and the loss of function of one or more isoforms can not be compensated by the function of others. Data obtained from this study indicates the possible critical role of soluble pyrophosphatases during plant development and stress response.
Keywords: Inorganic Pyrophosphate; Expression Analysis by Real-time PCR; Abiotic Stress; Mechanical Wounding; Double RNAi Knockdown; Digital Northern Analysis; İnorganik Pirofosfat; Gerçek-zamanlı PCR ile Ekspresyon Analizi; Abiyotik Stres; Çift ​​RNAi Demonte; Mekanik Yaralama; Dijital Northern Analizi